MEMBENTUK KARAKTER KEBANGSAAN MELALUI DUNIA VIRTUAL: STUDI KASUS REPLIKASI SITUS SEJARAH DAN MONUMEN DI MINECRAFT OLEH KOMUNITAS INDONESIA - Faris Hidayatjati, Utsman; Setio Nugroho, Arif; Dharmawan, Husein; Abdul Halim, Hisyam; Firmansyah, Akmal (Prosiding Temu Ilmiah Nasional Guru, 2026)
This study aims to examine how the replication of Indonesian historical sites and monuments in Minecraft by a local community can serve as an educational medium for students to shape the national character of the younger generation. This study highlights Minecraft's role as a creative space where Indonesian history and culture are digitally revived. Through the process of rebuilding historical sites in the game, students not only learn about the nation's history but also foster a sense of pride and love for their homeland. The research used a qualitative case study approach. Data were collected through participant observation on the Indonesian community's Minecraft server, documentation in the form of screenshots, videos of the construction process, and archives of public conversations, as well as content analysis of the resulting visual and narrative materials. Data analysis techniques used the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing, with validation through triangulation of sources and techniques. The results show that this virtual world can be an engaging and interactive learning medium, especially for the younger generation who are more familiar with digital technology. These Minecraft activities help strengthen national identity while introducing important values ​​in Indonesian history in a fun and accessible way. This research opens new opportunities for character education and cultural preservation through digital technology.